Perencanaan dan Penganggaran Responsif Gender terhadap Efektivitas Pelaksanaan Anggaran Organisasi Perangkat Daerah - Luawo, Vera Vebrianti; Saprudin, Saprudin; Junus, Onong; Hasan, Wahyudin (Universitas Gorontalo, 2025)
This study aims to analyze the effect of Gender-Responsive Planning and Budgeting on the effectiveness of budget implementation in Regional Government Organizations (OPD) in Gorontalo Regency. Involving 64 respondents from 32 OPDs and using multiple regression analysis, the results show that Gender-Responsive Planning does not have a significant effect due to the mismatch between budget realization and the planned targets. In contrast, Gender-Responsive Budgeting has a significant effect; however, limited budget allocations, particularly the decrease in General Allocation Funds (DAU), hinder gender equality programs. Therefore, the Inspectorate’s supervision is essential to ensure consistency between planning, budgeting, and budget implementation.